Biomechanical models for human gait analyses using inverse dynamics formulation - Moreira, Pedro (2013)
The main goal of this work is to present planar biomechanical multibody models, suitable to be used in inverse dynamic analyses. The proposed approach is straightforward and computationally efficient for the study of different human gait scenarios for normal and pathological. For this, a biomechanical model of the lower limb of the human body was developed. The biomechanical model consists of three bodies (thigh, calf and foot), corresponding to relevant anatomical segments of lower limb. These three rigid bodies are connected by revolute joints and described by eight natural coordinates, which are the Cartesian coordinates of the basic points located at the joints (hip, knee, ankle, metatarsal- phalangeal). The anthropometric dimensions of the model correspond to those of a normal male of 1.77 m and 80.0 kg. The total biomechanical system encompasses 5 degrees of freedom: 2 degrees if freedom for hip trajectory, 1 degree of freedom for hip flexion-extension motion, 1 degree of freedom for knee flexion-extension and 1 degree of freedom for ankle plantarflexion- dorsiflexion. The developed model was applied to solve an inverse dynamics problem of human motion. Therefore, the main objective of this simulation is to determine the joint moments-of- force and the joint reaction forces during an entire gait cycle, in order to compare with literature data.